Albuminuria, Hypertension, and Reduced Kidney Volumes in Adolescents Born Extremely Premature - Sanderson, Keia R.; Chang, Emily; Bjornstad, Erica; Hogan, Susan L.; Hu, Yichun; Askenazi, David; Fry, Rebecca C.; O'Shea, T. Michael (Frontiers in Pediatrics, 2020)
BACKGROUND: Premature birth is associated with decreased nephron number and an increased risk for chronic kidney disease (CKD). To inform the development of guidelines for kidney follow up of children born prematurely, we undertook a study of individuals born extremely preterm, with the aim of characterizing the prevalence and predictors of microalbuminuria, elevated blood pressure, and/or abnormal kidney volume in adolescence. METHODS: Study participants (n=42) were born before 28 weeks of gestation and were enrolled at birth in the Extremely Low Gestational Age Newborns (ELGAN) study. When participants were 15 years old, we obtained 2 manual blood pressures, a spot urine microalbumin measurement, and sonographic measurements of kidney length and volume. RESULTS: Of the 42 participants, 60% were male, 52% were Caucasian (18% Hispanic) and 43% were African-American. Their median age was 15 (IQR 15, 15.3) years. In 33.3% of the cohort, blood pressure was elevated (>120/80mmHg). Microalbuminuria (>30mg/g) was present in 11.9% of the cohort, and kidney volume below the 10th percentile of normative data was present in 14%. Twenty-one (50%) of the sample had at least one kidney abnormality (microalbuminuria, elevated blood pressures, and/or kidney hypoplasia); these individuals were more likely to have experienced neonatal hypotension [55% vs 17% among those with no kidney abnormality, p=0.02]. CONCLUSIONS: Half of adolescents in this extremely low gestational age cohort have at least one risk factor of kidney disease (reduced kidney volume, microalbuminuria, and/or elevated blood pressures) at 15 years of age. This study suggests the importance of monitoring kidney outcomes in children after extremely preterm birth, especially those with a history of neonatal hypotension.